Plasmodium vinckei genomes provide insights into the pan-genome and evolution of rodent malaria parasites - Ramaprasad, Abhinay; Klaus, Severina; Douvropoulou, Olga; Culleton, Richard; Pain, Arnab (BMC biology, 2021)
Rodent malaria parasites (RMPs) serve as tractable tools to study malaria parasite biology and host-parasite-vector interactions. Among the four RMPs originally collected from wild thicket rats in sub-Saharan Central Africa and adapted to laboratory mice, Plasmodium vinckei is the most geographically widespread with isolates collected from five separate locations. However, there is a lack of extensive phenotype and genotype data associated with this species, thus hindering its use in experimental studies.